FIXED VS REMOVABLE APPLIANCE ORTHODONTIC - Tita Ratya Utari (Dental reasearch exhibition and meeting, 2012)
orthodontic treatment can be performed by using a removable appliance and fixed appliance or the combination of removable and fixed appliance. fixed appliance is more rapidly evolving and used curently. however fixed orthodontic appliance is relatively more expensive and complex that not every orthodontic case can be managed by this method.